2022
DOI: 10.1097/md.0000000000030244
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ultrasound as a promising diagnostic tool for stroke-related sarcopenia: A retrospective pilot study

Abstract: Stroke patients undergo extensive changes in muscle mass which lead to stroke-related sarcopenia. Stroke-related sarcopenia has a significant impact on the functional outcome of stroke survivors. So, it is important to measure muscle mass in stroke patients. This study aimed to examine the correlation between ultrasonographic quadriceps muscle thickness (QMT) and dualenergy X-ray absorptiometry (DXA) derived appendicular lean mass (ALM) in patients with acute hemiplegic stroke. Twenty five participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study is the first one to assess the link between ultrasonographic measurements (MT, CSA) of BB and total muscle mass as measured by BIA in hospitalized older patients. Biceps brachii was used as an easier and more time-efficient alternative for the more commonly used rectus femoris and vastus lateralis [31][32][33][34] and the results obtained are promising. However, it must be taken into account that this is a pilot study, and the results must be confirmed in larger samples.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first one to assess the link between ultrasonographic measurements (MT, CSA) of BB and total muscle mass as measured by BIA in hospitalized older patients. Biceps brachii was used as an easier and more time-efficient alternative for the more commonly used rectus femoris and vastus lateralis [31][32][33][34] and the results obtained are promising. However, it must be taken into account that this is a pilot study, and the results must be confirmed in larger samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TMT was calculated from CT images, but TMT can be measured using ultrasonography and MRI as well [ 21 , 30 ]. Ultrasonography has been used for nutritional status assessment, and the technology has been improved [ 31 , 32 , 33 ]. Ultrasonography also has potential uses for swallowing assessment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%